Remembering the personal past descriptions of autobiographical memory - Ross, Bruce M. (New York, New York Oxford University Press, 1991)
The impetus for this book is the belief that a comprehensive description of autobiographical memory in both form and function must be an interdisciplinary endeavour. The author examines motivation and emotion as components of human memory and assembles sources previously ignored by psychologists.
1. Introduction -- 2. Memory Observed by Introspection -- 3. Freud's Theory of Memory -- 4. Additional Freudian Memory Concepts -- 5. Psychoanalytic Continuations -- 6. Some Psychoanalytic Offshoots: Summarizing Trends -- 7. Developmental Memory Theories -- 8. Sociological and Historical Perspectives -- 9. Memory Transmission and Cultivation -- 10. Conclusions and Possibilities.
Includes bibliographical references (pages 231-238) and index.
Keywords: Autobiographical memory